MAP Kinase Phosphatase-1 Protects against Inflammatory Bone Loss - Sartori, R.; Li, F.; Kirkwood, K. L. (Sage Publications Inc, 2009)
The mitogen-activated protein (MAP) kinase phosphatase (MKP) family plays an important function in regulating the pro-inflammatory cytokines by deactivating MAP kinases. MKP-1 is essential for the dephosphorylation of p38 MAP kinase that regulates expression of IL-6, TNF-alpha, and IL-1 beta. We hypothesized that MKP-1 regulates inflammatory bone loss in experimental periodontitis. Wild-type and Mkp-1(-/-) mice received A. actinomycetemcomitans LPS injection in the palatal region or PBS control 3 times/wk for 30 days. Mice were killed, and maxillae were assessed by microcomputed tomography, histological analysis, and TRAP staining for measurement of bone loss, extent of inflammation, and degree of osteoclastogenesis. Results indicated that, in LPS-injected Mkp-1(-/-) mice, significantly greater bone loss occurred with more inflammatory infiltrate and a significant increase in osteoclastogenesis compared with Mkp-1(-/-) control sites or either wild-type group. Analysis of these data indicates that MKP-1 plays a key role in the regulation of inflammatory bone loss.
Keywords: MKP-1; innate immunity; LPS; periodontal disease